2000
DOI: 10.1002/1096-9861(20001127)427:4<593::aid-cne7>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Topography and associations of luteinizing hormone-releasing hormone and neuropeptide Y-immunoreactive neuronal systems in the human diencephalon

Abstract: Neuropeptide Y (NPY) potentiates the effect of luteinizing hormone-releasing hormone (LHRH) on luteinizing hormone secretion in several species, including human. In addition to the pituitary sites, the interactions of the NPY and LHRH systems may involve diencephalic loci. However, the morphologic basis of this putative communication has not yet been elucidated in the human brain. To discover interaction sites, the distribution and connections of LHRH and NPY-immunoreactive (IR) neuronal elements in the human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 80 publications
4
46
0
Order By: Relevance
“…The distribution of LHRH-IR elements were in good agreement with our previous studies (31)(32)(33)(34)(35)(36). LHRH-IR perikarya were located mainly in the medial preoptic area and in the infundibulum/median eminence (Fig.…”
Section: Lhrh Systemsupporting
confidence: 91%
See 1 more Smart Citation
“…The distribution of LHRH-IR elements were in good agreement with our previous studies (31)(32)(33)(34)(35)(36). LHRH-IR perikarya were located mainly in the medial preoptic area and in the infundibulum/median eminence (Fig.…”
Section: Lhrh Systemsupporting
confidence: 91%
“…The distribution of LHRH-IR elements is well known in the human diencephalon (31)(32)(33)(34)(35)(36). In contrast to these data, studies regarding the pattern and morphology of enkephalin system were restricted to the rat brain (27)(28)(29).…”
mentioning
confidence: 99%
“…Subsequent studies linked this phenomenon to a direct regulation of the HPG axis, particularly at the level of the GnRH neuron (23,213,253,254) and specifically in the potentiation of the preovulatory GnRH-induced luteinizing hormone surge (1,14,125,217). This interaction between NPY and GnRH neurons is supported by neuroanatomic studies that found ARC NPY-and NPY receptor immunoreactive fibers in close proximity to GnRH perikarya in the preoptic area (65,66,154,166).…”
Section: New Insights Into Reproduction Using Neuronal Cell Modelsmentioning
confidence: 92%
“…Since previous studies revealed numerous juxtapositions between LHRH neurons [21], it is a common consensus that these close associations may represent synaptic connections and they may be responsible for the pulsatile release of LHRH in numerous species. Similarly to the LHRH system, the juxtapositions described in the present paper may represent the morphological basis of the synchronized activity of the GHRH neurons.…”
Section: Discussionmentioning
confidence: 99%